The Relationship Of Family Support To The Level Of Ability To Perform Daily Activities In Stroke Patients In Imelda Pekerja Indonesia General Hospital - Sagala, Deddy Sepadha Putra; Damanik, Hamonangan; Hutagaol, Aureliya; Dewi, Ratna; Pasaribu, Sri Delvia (CV. Devitara, 2024)
Stroke is one of the leading causes of death and third cause of disability in the world. Someone who has a stroke will have limitations in carrying out daily activities or Activity Of Daily Living (ADL) and support from family both in physical, psychological and emotional forms is needed by stroke patients The purpose of this study was to determine family support for the level of ability to carry out daily activities in stroke patients at Imelda Pekerja Indonesia General Hospital. This type of research is quantitative research with correlational methods and Cross Sectional approach design. This research was conducted in July-August 2023 at the Imelda Hemodialysis Room of Imelda Pekerja Indonesia General Hospital. This study used NonProbability sampling technique using purposive sampling method, so that the total research sample was 30 respondents. The instrument used in this study was a questionnaire. Data analysis using univariate and bivariate analysis with statistical tests (Chi Square Test) in the SPSS application. The results of the study showed the results of the Chi-Square statistical test with a significant value (p) value of 0.01 or p< 0.05. The conclusion in this study is that there is family support for the level of ability to carry out daily activities in stroke patients at Imelda Pekerja Indonesia General Hospital in 2023.